Pelabelan L(2,1) pada Graf Sierpinski S(n,k) - Sagala, Yuri C.; Susiana, Susiana (Jurnal Sains Indonesia, 2018)
Labeling L (2; 1) on a graph G is the function f of the set of vertices V (G) to the set of all non-negative numbers so that âf (u) - f (w) â â¥ 2 if d (u; w) = 1 and âf (u) - f (w)â â¥ 1 if d (u; w) = 2. The labeling number L (2; 1) of a graph G is the smallest k number so G has labeling L (2; 1) with max {f (v): v Ð V (G) g} = k. The Sierpinski Graph is a form of expansion graph specifically from a complete graph. This study shows labeling on Sierpinski graph using Chang-Kuo algorithm and obtained the values L (2; 1) {S (n; 2)} = 4 and the value of L (2; 1) {S (n; 3)} = 6 for n â¥ 2, with L (2; 1) G is the smallest maximum number labeling L (2; 1) from a graph G.